Enhanced CANDU reactor with heat upgrade for combined power and hydrogen production - El-Emam, Rami S.; Dincer, Ibrahim; Zamfirescu, Calin (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Nuclear energy is considered a key alternative to overcome the environmental issues caused by fossil fuels. It offers opportunities with an improved operating efficiency and safety for producing power, synthetic fuels, delivering process heat and for multi-generation applications. The high-temperature nuclear reactors, although possess great potential for integration with thermochemical water-splitting cycles for hydrogen production, are not yet commercially established. Current nuclear reactor designs providing heat at relatively low temperature can be utilized to produce hydrogen using thermochemical cycles if the temperature of their thermal heat is increased. In this paper, a hybrid chemical-mechanical heat pump system is proposed for upgrading the heat of the Enhanced CANDU (EC6) reactor design to the quality required for the copper-chlorine (Cu -Cl) hybrid thermochemical water splitting cycle operating at 550-600 degrees C. A modification to the heat pump is proposed to bring the heat to temperature higher than 650 degrees C with operating coefficient of performance estimated as 0.65. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Nuclear power; Hydrogen production; Heat upgrade; Heat pump; Cu-Cl cycle; Chemistry; Electrochemistry; Energy & Fuels